Occupational exposure to N-nitrosamines and pesticides and risk of pancreatic cancer - Fritschi, Lin; Benke, G.; Risch, H.; Schulte, A.; Webb, P.; Whiteman, D.; Fawcett, J.; Neale, R. (BMJ Publishing Group, 2015)
Objectives Animal evidence shows that N-nitrosamines and similar xenobiotic compounds are pancreatic carcinogens. We aimed to determine whether occupational exposure to N-nitrosamines or to pesticides increases risk of pancreatic cancer development. Methods Participants (504 cases, 643 controls) in a population-based case-control study (The Queensland Pancreatic Cancer Study) provided data on demographic, medical and lifestyle factors and lifetime job histories. Specific questions were asked regarding work in rubber and leather industries, metalworking jobs and occupational or direct use of pesticides on animals or crops. An occupational hygienist reviewed this information (blind to case status) to assess likelihood of exposure to N-nitrosamines and pesticides, and estimated level and frequency of such exposures. Results No associations were found for risk of pancreatic cancer and occupational exposure to N-nitrosamines (OR=0.85, 95% CI 0.51 to 1.42) and no associations were seen with level or frequency of exposure. No associations were observed for ever exposure to pesticides in general (OR=0.90, 95% CI 0.61 to 1.33) or to any of the pesticide subgroups. Stratification by history of cigarette smoking did not change these results. Conclusions This comprehensive analysis of a large case-control study does not support an association between occupational exposure to N-nitrosamines or pesticide use and risk of pancreatic cancer.